International Education System in Pedagogical Studies - Indri Pangastuti; Yaya Sunarya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Team of the Directorate of the Educator Profession, Directorate General for Improving the Quality of Educators and Education Personnel (2006) has substantively formulated pedagogical competencies which include the ability to understand students, design and implement learning, evaluate learning outcomes, and develop students to actualize the various potentials they have. Education is